The role of alpha-7 nicotinic receptors in food intake behaviors - McFadden, Kristina L.; Cornier, Marc-Andre; Tregellas, Jason R. (Frontiers in Psychology, 2014)
Nicotine alters appetite and energy expenditure, leading to changes in body weight. While the exact mechanisms underlying these effects are not fully established, both central and peripheral involvement of the alpha-7 nicotinic acetylcholine receptor (α7nAChR) has been suggested. Centrally, the α7nAChR modulates activity of hypothalamic neurons involved in food intake regulation, including proopiomelanocortin (POMC) and neuropeptide Y (NPY). α7nAChRs also modulate glutamatergic and dopaminergic systems controlling reward processes that affect food intake. Additionally, α7nAChRs are important peripheral mediators of chronic inflammation, a key contributor to health problems in obesity. This review focuses on nicotinic cholinergic effects on eating behaviors, specifically those involving the α7nAChR, with the hypothesis that α7nAChR agonism leads to appetite suppression. Recent studies are highlighted that identify links between α7nAChR expression and obesity, insulin resistance, and diabetes and describe early findings showing an α7nAChR agonist to be associated with reduced weight gain in a mouse model of diabetes. Given these effects, the α7nAChR may be a useful therapeutic target for strategies to treat and manage obesity.